Explore the attitudes of children and adolescent parents towards the vaccination of COVID-19 in China - Lin Wang; Wen Wen; Chen Chen; Jiake Tang; Chunyi Wang; Mengyun Zhou; Yongran Cheng; Xingwei Zhang; Mingwei Wang; Zhanhui Feng; Weiqian Wang (BMC, 2022)
Abstract Background With the increasing incidence of asymptomatic carriers or milder symptoms, children and adolescents are likely to become a silent source of infection. In view of the efficacy and safety of vaccines in the treatment of novel Coronavirus pneumonia, population-wide vaccination will be an inevitable trend to control the spread of COVID-19. However, there is no survey on the attitudes of Chinese parents of children and adolescents towards their children's COVID-19 vaccination. Methods We used online questionnaires to find out the attitudes of Chinese parents toward their children's immunization against COVID-19. Logistic regression was used to explore the influencing factors. Results A total of 2019 parents participated in the survey. Overall, 74.38% parents said they would actively get vaccinated, 8.90% refused to get vaccinated, 4.60% said they would delay vaccination and 12.12% were still undecided. Conclusions In general, Chinese parents have a high desire to be vaccinated against COVID-19, and most parents have a positive attitude towards their children's vaccination. However, many people still hesitate or even refuse to be vaccinated. Education background, attitudes towards children's vaccination, children's age, recent illness and other factors have a certain impact on Chinese parents of children and adolescents towards their children's COVID-19 vaccination.